Spectrophotometric Determination of Trace Amounts of Phenylhydrazine in Water and Biological Samples After Preconcentration by the Cloud Point Extraction Method - Reza Zarei, Ali; Ali Zarei, Mohammad (Asian Journal of Chemistry, 2010)
A cloud point extraction method for preconcentration of ultra-trace quantities of phenylhydrazine as a prior step to its determination by spectrophotometry has been developed. The method is based on the extraction of phenylhydrazone, the colored product of the reaction of phenylhydrazine with p-nitrobenzaldehyde, in the presence of electrolyte as an inducing phase separation factor. The anionic surfactant sodium dodecyl sulfate (SDS) and nonionic surfactant Triton-X-114 were used as mixed micelle-mediated. The phenylhydrazone concentrated in surfactant rich phase was then determined spectrophotometrically at 427 nm. The optimal extraction and reaction conditions (e.g. surfactant, reagent and electrolyte concentrations and centrifuge time) were studied and the analytical characteristics of the method (e.g. limit of detection, linear range, preconcentration, and improvement factors) were obtained. Linearity was obeyed in the range of 4.0-600 ng mL-1 of phenylhydrazine and the detection limit of the method is 1.80 ng mL-1.The interference effect of some cations, anions, and organic compounds was also tested. The method was successfully applied to the determination of phenylhydrazine in water and biological samples.